Nutrtional Status and its Correlation with Academic Performance of School Going Children - Waheed Ullah, Sara Jamil Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The nutritional status of the children is satisfactory in Asian countries like Pakistan however the prevalence of malnutrition is observed to decrease because of the various health programs at national and international level in order to improve the health status of growing children. The aim of this study was to assess the prevalence nutritional status and correlation between nutritional status of students and their academic performance of school going children in Timergara. Methodology: This cross sectional study was conducted by administering and filling the questionnaire from 400 children, 200 from private and 200 from public sector schools of ages 6 to 11 years in different public and private sector schools of tehsil Timergara Lower Dir, KPK. Nutritional status of children was calculated by anthropometric method and compared with WHO growth chart. Academic performance was calculated from the percentage of the marks obtained in the last annual exam. Data analysis was done using IBM SPSS 24.0. Results: The prevalence of male gender were 61% and female gender were 39%. The prevalence of stunting, underweight, thin and Overweight+Obese were25.0 %, 17.0%, 7.5 % and 5.0% correspondingly. The low level of educational performance was significantly higher among the stunted (60.0%), underweight (38.2%), thin (33.3%) and Overweight+Obese (10.0%)children than that of the normal children.The low level of educational performance was significantly higher (p < 0.05) among the stunted, underweight and wasted children than that of the normal children. Conclusion: The nutritional status of school going children of Lower Dir, KPK was satisfactory however emphasis on the awareness regarding nutrition must be given. Keywords: Private, Public, School going children, Nutritional status